Light-induced phosphorylation of a membrane protein plays an early role in signal transduction for phototropism in Arabidopsis thaliana. - Reymond, P (1992)
Blue light is known to cause rapid phosphorylation of a membrane protein in etiolated seedlings of several plant species, a protein that, at least in etiolated pea seedlings and maize coleoptiles, has been shown to be associated with the plasma membrane. The light-driven phosphorylation has been proposed on the basis of correlative evidence to be an early step in the signal transduction chain for phototropism. In the Arabidopsis thaliana mutant JK224, the sensitivity to blue light for induction of first positive phototropism is known to be 20- to 30-fold lower than in wild type, whereas second positive curvature appears to be normal. While light-induced phosphorylation can be demonstrated in crude membrane preparations from shoots of the mutant, the level of phosphorylation is dramatically lower than in wild type, as is the sensitivity to blue light. Another A. thaliana mutant, JK218, that completely lacks any phototropic responses to up to 2 h of irradiation, shows a normal level of light-induced phosphorylation at saturation. Since its gravitropic sensitivity is normal, it is presumably blocked in some step between photoreception and the confluence of the signal transduction pathways for phototropism and gravitropism. We conclude from mutant JK224 that light-induced phosphorylation plays an early role in the signal transduction chain for phototropism in higher plants.